Pengaruh Pengetahuan Discharge Planning Terhadap Kesiapan Pasien Asma Menghadapi Pemulangan Di RSUD Dr. M.Yunus Bengkulu - Andari, Fatsiwi Nunik; Kusuma Wijaya, Andri; Nugraha, Prihantara (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2023)
Background: Asthma is one of the non-communicable diseases and belongs to the group of chronic lung diseases. The patient’s lack of knowledge about asthma which causes asthma to recur, so a patient’s return plan is needed so that the patient really feels healthy and is ready to go home. Methods: The research is a quantitative pre-experiment study with one group pre and post test design. The population in this study were all asthma patients treated at RSUD Dr. M.yunus with total 64 people. The sample is 15 respondents with purposive sampling technique. Data were analyzed using nonparametric analysis Wilcoxon test. Results: before being given discharge planning knowledge of on the readiness of asthma patients facing repatriation there were 73.3% ready to face repatriation and after being given knowledge of discharge planning there has been increase 86.7%. Based on the results of the Wilcoxon test it was obtained that p-value = 0.001 which means there is a significant influence of discharge planning knowledge on the readiness of asthma patients facing repatriation. Keywords : Asthma Patients, Knowledge of Discharge Planning, Repatriation Readiness